Arsip Dinamis Mendukung Whole of Government di Perguruan Tinggi - Agus Sediadi Tamtanus (Journal of Governance, 2019)
One of the Agenda 3 subject material, for participant in basic training of civil servant candidates (CPNS) Group III is Whole of Government (WoG). These CPNS are prospective young lecturers at various universities in Indonesia. The presence of WoG training subject, it is hoped that the prospective young lecturers can quickly actualize the concepts and implementation of WoG concepts in higher education in a policy perspective in Indonesia. Problems faced by Indonesia universities is the website ranking is still low based on Webometrics. The development of a website must have sufficient insight into the concept of Dynamic Archives, the concept of e-Government and the concept of WoG that are interrelated and have an impact. It is because of universities have vision and mission to become World Class University (WCU), and one of efforts to reach that by increasing the international ranking in Webometrics.